Effect of ball milling on the carbon sequestration efficiency of serpentinized peridotites. (May 2018) - Rigopoulos, Ioannis; Delimitis, Andreas; Ioannou, Ioannis; Efstathiou, Angelos M.; Kyratsi, Theodora
Highlights: Ultrafine materials were produced via ball milling (BM) of an altered harzburgite. The particle size was reduced to the nanoscale range after the BM process. The optimum conditions are 16 h of BM with 50 wt% ethanol as process control agent. The CO2 uptake of the initial rock material was increased by a factor of 4.5. BM promotes the formation of more strongly bound carbonate species. Abstract: Mineral carbonation has been suggested as a safe carbon capture and storage (CCS) strategy for the mitigation of climate change. This study investigates the effect of ball milling on the CO2 sequestration capacity of peridotites, which are among the most promising readily available lithologies for CCS on the Earth's surface. A partially serpentinized harzburgite from the Troodos ophiolite (Cyprus) was subjected to different degrees of ball milling to produce nanoscale ultramafic powders with enhanced CO2 uptake. The optimum ball milling conditions were found (16 h of wet ball milling with 50 wt% ethanol as process control agent) through CO2 chemisorption followed by temperature-programmed desorption (CO2 -TPD) experiments. The results clearly showed that the CO2 uptake of the initial rock material was increased by a factor of 4.5 after ball milling. Detailed characterization of the unmilled and ball-milled samples indicated that this enhancement is mainly attributed to (i) the reduction of particle size down to the nanoscale range and (ii) the structural disordering of the constituent Mg-silicate minerals due to mechanical deformation.